WILDLIFE EX-SITU CONSERVATION : FORENSICS, BIOBANKING, ZOONOTIC DISEASES AND CAPTIVE BREEDING - AMAL GHAZALI, NASRON; ANA MARIA, ABD. RAHIM; BADMANATHAN, MUNISAMY; DAVID, MAGINTAN; DONNY, YAWAH; FRANKIE THOMAS, SITAM; HARTINI, ITHNIN; JEFFRINE ROVIE RYAN, JAPNING; KAYAL VIZI, KARUPPANNAN; KHAIRUL AMIRIN, MOHAMED; KHAIRUL NIZAM, KAMARUDDIN; MILLAWATI, GANI; et al. (Department of Wildlife and National Parks (PERHILITAN) Peninsular Malaysia, 2023)
Wildlife ex-situ conservation is a complete process of securing populations outside natural habitats. Tools like captive breeding, population genetics, artificial insemination and many others are key elements in this conservation practice. This book compiles all the advancements in ex-situ conservation via the application of forensics, captive breeding, molecular genetics, disease control and husbandry management by the Department of Wildlife and National Parks (PERHILITAN) Peninsular Malaysia. A very precise and comprehensive explanation of each component is presented in this book. Those components include An Overview of ExSitu Conservation; Wildlife Forensics for Combating Wildlife Crime; Wildlife Biobanking; Wildlife Disease Surveillance; Wildlife Conservation; Wildlife Rescue, Rehabilitation and Release; Wildlife Husbandry Management and Way Forward of PERHILITAN’s ultimate goal in ex-situ conservation. All the information generated in this book will be valuable guidance for wildlife conservationists, policymakers, stakeholders and scholars. The authors of this book comprise a team with extensive experience and a wide range of skills, which make them highly qualified to publish the first-ever book on Ex-Situ Conservation in Peninsular Malaysia.